KETERPADUAN STRUKTUR DRAMATIK PERTUNJUKAN WAYANG KULIT LAKON SUDHAMALA - GR. Lono Lastoro Simatupang; Timbul Haryono; S. Soetarno (Institut Seni Indonesia Surakarta, 2014)
Wayang performance can be used for the sake of ritual ceremony ruwatan. The story of wayang performanceruwatan lakon Sudamala comes from kidung Sudamala. The literature work is sacred. Besides in literaturework, Sudamala story also can be seen visually in the relief sculpture of Candi Sukuh (Central Java) andTegowangi (East Java). The research problem is how the integration of dramatic elements in lakon Sudamalapresented by Ki Purbo Asmoro. The purpose of the discussion is to describe the dramatic elements in lakonSudamala. Lakon Sudamala is researched by using textual approach from the dramatic structure as well asthe treatment elements. Based on the approach, the result found is that the presented structure hasn’t beenas strict as the balungan lakon of the palace tradition even it can be a new treatment presentation. The onenight wayang performance is not anymore treated traditionally but it presents a creative treatment of thescene. It can be seen from ginem that the chosen words is suitable to the characters’ characteristics,pocapan that only uses short words, and the presented janturan that seems to be a kind of janturan alit thatis janturan that its expression is relatively short.Keywords: wayang performance, Sudamala, tekstual, dramatic structure